Changes in Physicochemical Properties of Soil Encourage the Invasion Establishment and Carbon Dynamics of Lantana camara from Doon Valley, Western Himalaya, India - Gautam Mandal; Shambhu P. Joshi (Aceh International Journal of Science and Technology, 2014)
Abstract - Lantana camara L. is a recognized weed of worldwide significance due to its widespread distribution and impacts on nature conservation. In this study physicochemical properties of soil were analysed from different high and low Lantana infested areas. Significant site effect was frequently observed than effect due to invasion status. The present study tested the impact of soil properties in the measured and calculated attributes of Lantana by randomly sampling soil from the highly invaded and less invaded sites in different habitats using the Modified Whittaker plot design. Ten samples were collected at high invaded and ten at less invaded sites per habitat totalling to 120 which were obtained and analysed. One way analysis of variance (ANOVA) results indicated that edaphic factors such as soil pH, total nitrogen, soil organic carbon, Phosphorus and Potassium content positively influenced the growth of Lantana and helped in the further invasion process. These factors were also positively influencing the measured and calculated attributes of Lantana such as canopy coverage, average crown diameter, shrub canopy area, phytovolume and biomass from all sites. However some attributes like shrub height and stem diameter were negatively influenced by these soil factors. The level of these soil nutrients was found elevated in all Lantana invaded sites as compared to less invaded sites. The present results reveal that Lantana invasion can not only significantly improve the soil nutrient level but also positively increase the chances of its further invasion with more copious plant attributes.